Carbotermica reduction kinetics of the chalcopyrite of complex Marañón - Lovera, Daniel (2010)
Taking the Peru a leadership in the production of metals in the world, the world’s largest producer of silver, the second of copper and zinc, and the sixth in gold, it is necessary to develop intensive metallurgical research to give greater technological value to our concentrates. In the framework of clean technologies direct reduction of sulphides is of interest in metallurgical processes for obtaining base metal. In this investigation shows results of the kinetics of direct reduction of the chalcopyrite of complex marañón with coal in the presence of dolomite as an opportunity to produce copper from a sulphide avoiding air pollution. We studied the effect of the variables involved in the reduction carbotermica: Temperature, reasons molars of reactants, being kinetic model that we describe the phenomenology of reduction process of the chalcopyrite.